How HCI concepts are used in articles featuring interactive digital arts: a literature review. - Batista, Nathan Lima; Monteiro, Ingrid Teixeira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Technological advancement has enabled the creation of new forms of digital art. Consequently, interactive digital art is becoming increasingly common. Additionally, some artists are concerned with the human aspects of the audience and their experiences, such as the feelings and emotions evoked by their artworks. As a result, there is a strong relationship between this type of art and human-computer interaction (HCI), which aims to understand the use of interactive systems in a specific context.This work presents a systematic literature review with the objective of identifying the HCI concepts present in the selected articles from the review. It aims to assist future research that seeks to comprehend how articles on interactive digital art utilize HCI concepts, and also to identify the most recurrent types of interactive digital art. Furthermore, it provides insights for the emergence of future research in relatively unexplored areas.